Struktur Resistivitas Dangkal Sebagai Upaya Mitigasi Bencana Pergerakan Tanah - Bambang Wijatmoko; Budy Santoso; Eleonora Agustine; Yudi Rosandi (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2019)
Cisempur village is located at the slope of Mount Geulis, having a very variated morphology from gentle slopes to very steep ones. Due to the high demand for settlements the land use change can not be avoided. The steepness of the slope, the decrease of the number of vegetations, and the increase of load from buildings may induced land slide occurrence. This problem motivate us to perform measurement at the area, in order to uncover the information about the level of stability and the land carrying capacity, through the study of the subsurface rock layering condition. In this work, we present the shallow resistivity by means of Electrical Resistivity Tomography (ERT) method in two measurement lines. The obtained data is processed using 2D inversion method, in order to obtain the layering structure cross-section. The interpretation of the results suggest the existence of sandstone, which is normally associated with the location of aquifer and tuffaceous clay. The tuffaceous may function as the slide plane in the land slide event. The interpretation also shows that the carrying capacity decrease very extremely at the settlement site, which is indicated by the land displacement. This information has to be socialized and transferred to the inhabitant, in order to build awareness, and the land slide disaster mitigation can be carried out.